Formation of Self-assessing Actions of education achievements at Russian Language Teaching (Proceedings of Southern Federal University. Philology, 2018)
Larisa V. Cherepanova (Chita, Russian Federation)The problem of the formation of schoolchildren’s actions of selfevaluation of educational achievements in teaching the Russian language is justified as relevant, aimed at achieving the goals of GEF. The concept of self-evaluation in the aspect of teaching is defined, the essence of the action of self-evaluation is described. Materials developed by the author for the exercises of the Russian language textbook edited by A.A. Leontiev, on the formation of the action of self-evaluation of educational achievements are presented.Key words: self-evaluation, self-esteem, universal educational action, subject of teaching, reflection, teaching Russian, educational achievements.